CFTR Rescue in Intestinal Organoids with GLPG/ABBV-2737, ABBV/GLPG-2222 and ABBV/GLPG-2451 Triple Therapy - de Poel, Eyleen; Spelier, Sacha; Korporaal, Ricardo; Lai, Ka Wai; Boj, Sylvia F.; Conrath, Katja; van der Ent, Cornelis K.; Beekman, Jeffrey M. (Frontiers in Molecular Biosciences, 2021)
Cystic fibrosis transmembrane conductance regulator (CFTR) modulators have transformed the treatment of cystic fibrosis (CF) by targeting the basis of the disease. In particular, treatment regimen consisting of multiple compounds with complementary mechanisms of action have been shown to result in optimal efficacy. Here, we assessed the efficacy of combinations of the CFTR modulators ABBV/GLPG-2222, GLPG/ABBV-2737 and ABBV/GLPG-2451, and compared it to VX-770/VX-809 in 28 organoid lines heterozygous for F508del allele and a class I mutation and 7 homozygous F508del organoid lines. The combination ABBV/GLPG-2222/ABBV-2737/ABBV/GLPG-2451 showed increased efficacy over VX-770/VX-809 for most organoids, despite considerable variation in efficacy between the different organoid cultures. These data differences in CFTR restoration between organoids with comparable genotypes underline the relevance of continuing to optimize the ABBV/GLPG-Triple therapy, as well as the in vitro characterization of efficacy in clinically relevant models.